The Evolution of Public Surveillance Systems in Europe - Tóth, Levente (Magyar Rendészet, 2023)
Video surveillance systems are used today in many parts of the world in public spaces. Although most publications date the appearance of the systems in public spaces to the 1980s, the use of the systems by the British police dates back 60 years. However, the actual spread of these systems has only been significant since the 1990s, as the development of technology made it possible to produce images of a quality that can be well utilised for the suppression and detection of crime through constant and intensive surveillance of public spaces at a cost-effective price. The speed of spread, size of infrastructure, mode of supervision and use, and the purpose of installation of the systems vary from country to country in Europe. This is mainly determined by the political, social, criminal, economic and legal context of the country.